A cleaner and sustainable method to recover vanadium and chromium from the leaching solution based on solvent extraction. Issue 3 (June 2022) - Ying, Ziwen; Song, Yue; Zhu, Keyu; Wu, Guixuan; Ju, Yun; Wei, Qifeng; Ren, Xiulian
Abstract: In the work, a cleaner and sustainable method to recover vanadium (V) and chromium (VI) from the leaching solution based on solvent extraction using amide as extractant was developed. In the method, V(V) and Cr(VI) in the chlorinated system were co-extracted in extraction section and then separated in stripping section. Different parameters were explored to determine the optimum conditions of co-extracting V and Cr. The final V and Cr extraction efficiency could reach above 99.5% and 99.9%, respectively. Vanadium and chromium in the loaded organic phase could be stepwise stripped selectively using 1.5 mol/L HCl and 0.5 mol/L NaOH, and final V and Cr stripping efficiency could reach above 99.8% and 99%, respectively. The purity of the V2 O5 product was 99.22% and the total recovery of vanadium was about 95%. The purity of the Cr2 O3 product was 98.66% and the total recovery of chromium was about 97%. The slope analysis method confirmed that V(V)-amide extraction complex in chlorinated system was H2 VO2 Cl3 R2 . ESI-MS and FT-IR spectrums further confirmed extraction mechanism. The reduction phenomenon of V(V) and Cr(VI) was investigated and internal mechanism was proposed. The work provided a cleaner and sustainable method to recover V and Cr from the leaching solution and to produce vanadium and chromium products. The cleaner and sustainable method process has potential application for treating other solution containing vanadium and chromium such as leaching solution of chromite, stone coal and vanadium containing waste catalyst. Graphical Abstract: ga1 Highlights: A cleaner and sustainable method for separation of V(V) and Cr(Ⅵ) was proposed. V(V) and Cr(Ⅵ) could be co-extracted and then separated in stripping section. The V-amide extraction complex in chlorinated system was confirmed as H2 VO2 Cl3 R2 . The reduction phenomenon of V(V) and Cr(VI) was investigated.